The Magician of Ridge Ruin: Insights into Ceremony and Status from Arrow Points and Bows. (1st October 2016) - Kamp, Kathryn A.; Whittaker, John C.; Bryce, William D.
Abstract : Stone tools and the perishable artifacts of which they are often components can be used to express complex social and ritual messages. A detailed analysis of projectile points, arrow shafts, and painted miniature bows from the burial of the so-called "Magician" of Ridge Ruin demonstrates the power of specific burial analyses to reconstruct the ritual and social context of a funeral ceremony. The Magician, an adult Sinagua male buried with ceremonial paraphernalia and other rare items, perhaps the richest burial ever discovered in the Puebloan Southwest, has been central to social interpretations of the region. Among unique aspects of the burial were a deposit of painted miniature bows and an assemblage of 434 projectile points, which have not been fully described before. These objects were deposited in the terminal phases of a complex mortuary ceremony by a large number of individuals, possibly members of a warrior sodality. In the broader context of the entire burial, the analysis reinforces a model of social heterarchy in which the Magician was especially important because he simultaneously obtained status and authority from several domains.